Diagnostic Evaluation of 18F-FDG PET/CT Imaging in Recurrent or Residual Urinary Bladder Cancer: A Meta-Analysis - Xue, Minmin; Liu, Liping; Du, Guanghui; Fu, Zhigang (Urology Journal, 2020)
Purpose: To assess the diagnostic accuracy of fluorine-18 fluorodeoxyglucose positron emission tomography combined with the computed tomography (18F-FDG PET/CT) in the detection of recurrent or residual urinary bladder cancer with meta-analysis. Methods: We searched PubMed/MEDLINE, Embase, Web of Science, CBM, CNKI, VIP, and Wanfang databases through October 2019. Two reviewers independently screened the full articles. The imaging findings were confirmed by either histopathology or clinical follow-up. Sensitivity, specificity likelihood ratio and diagnostic odds ratio were pooled with 95 % confidence intervals (CI). Overall test performance was summarized by a summary receiver operating characteristic (ROC) curve. The Meta-DiSc software (version 1.4) was used to perform the meta-analysis. Results: The meta-analysis included 7 studies. The pooled sensitivity and specificity of PET/CT for the detection of recurrent or residual urinary bladder cancer was 94.0% (95% CI: 91.0%–96.0%) and 92.0% (95% CI: 88.0%– 95.0%), respectively. Positive likelihood ratio, negative likelihood ratio and diagnostic odds ratio were 9.77 (95% CI: 4.91–19.41), 0.99(95% CI: 0.06–0.13) and 95.09 (95% CI: 47.96–188.53), respectively. When residual urinary bladder cancer was excluded, sensitivity changed slightly. Conclusion: This meta-analysis suggested that the diagnostic accuracy of PET/CT was good in detecting recurrent or residual urinary bladder cancer.